Coupled Eulerian-Lagrangian finite element method for simulating soil-tool interaction. (November 2018) - Zhang, Lingbo; Cai, Zongxi; Wang, Liwei; Zhang, Runxi; Liu, Haofei
Abstract : Simulation of soil-tool interaction is challenging due to large deformations of soil around the tool, unconstrained deformation of the free soil surface and the dynamic behaviour of soil-tool interaction at the interface. An application of a coupled Eulerian-Lagrangian finite element (CEL-FE) method to the simulation of soil-tool interaction is presented. By combining the merits of both the Lagrangian and the Eulerian formulations, large deformation and unconstrained deformation of soil and the dynamic behaviour of soil-tool interaction are simultaneously simulated. Firstly, interactions between the soil and vertical tines were simulated. The results showed that the predicted soil deformation and draft force were in reasonable agreement with published data from soil bin tests. Then, in order to further validate the feasibility and effectiveness of the CEL-FE method, interactions between the soil and inclined blades at different operating conditions were simulated. Results showed that the numerically simulated and experimentally measured draft forces exhibited similar trends and average values. In addition, the predicted soil deformation was in general agreement with experimental observations. Finally, an example of simulating soil-mouldboard interaction was given and preliminary results indicated that shape complexity of this tool was not a limitation for applying the CEL-FE method. The proposed CEL-FE method provides new possibilities for simulating soil-tool interaction and it is hoped that this method will help to contribute a better understanding of the soil-tool interaction process thereby improving the design of tillage tools. Highlights: An advanced CEL-FE method is presented for the simulation of soil-tool interaction. The large deformation and free deformation of soil are simulated simultaneously. The dynamic soil-tool interaction behavior at the interface is simulated. The CEL-FE method is convenient to use for tillage tools with complex shapes.